Spontaneous Rectus Sheath Hematoma in Pregnancy Complicated by the Development of Transfusion Related Acute Lung Injury: A Case Report and Review of the Literature - Jennifer Gibbs; Firas Bridges; Kiran Trivedi; John Vullo (Thieme Medical Publishers, Inc., 2016)
Abstract Background Rectus sheath hematoma (RSH) represents a rare, but serious cause of abdominal pain. Case Here we discuss the case of a healthy multigravida female who presented at 28 weeks gestation with spontaneous RSH. Conservative management with multiple blood transfusions led to the development of transfusion related acute lung injury (TRALI) and intensive care unit admission. She was managed with noninvasive ventilatory support, gradually improved, and was weaned of ventilation. After hospital discharge, she progressed to full term and delivered a viable male infant vaginally at 37 weeks gestation. Conclusion Review of the literature demonstrates 13 cases of RSH in pregnancy, including our own. No other cases were complicated by transfusion related morbidity. RSH and TRALI are rare, but life threatening entities that can complicate pregnancy.